Complexities of Candida Colonization and Oral Microbiome in Oral Lichen Planus: A Systematic Review and Meta-Analysis - Israyani; Christine Anastasia Rovani; Erni Marlina; Chung-Ming Liu (Dentistry Journal)
Background/objectives: Oral lichen planus (OLP) is a chronic autoimmune disorder affecting various age groups and is associated with multiple factors. Conventional therapies often encounter complications from opportunistic infections, particularly oral candidiasis. This study examines the relationships between Candida colonization and oral microbiome composition in OLP patients. Through meta-analysis, we clarify these interactions and their implications for OLP progression. Methods: The PICOS is a systematic research strategy, following PRISMA 2020 and MeSH descriptors: oral lichen planus, oral microbiome, oral fungal, and non-Candida oral fungal. Results: A search of CINAHL, EMBASE, PubMed, Science Direct, and Web of Science identified 313 studies. Twelve studies were suitable for a systematic review, with four appropriate for meta-analysis. Findings showed a significant association between OLP and oral microbiota, with an OR of 4.155 (95% CI: 1.278–13.511, p = 0.024). Although analyses of C. albicans and non-albicans species lacked significance, particular non-albicans species were noted. The subgroup analysis of oral microbiota approached significance, indicated by an OR of 11.739 (95% CI: 0.654–210.713, p = 0.059). Conclusions: This study highlights the roles of Candida species and the oral microbiota in OLP, revealing a complex interaction between Candida colonization and the oral microbiome.